Perioperative Blood Glucose Levels <150 mg/dL are Associated With Improved 5-Year Survival in Patients Undergoing On-Pump Cardiac Surgery: A Prospective, Observational Cohort Study. Issue 45 (November 2015) - Mansur, Ashham; Popov, Aron Frederik; Hanna, Ameen Abu; Bergmann, Ingo; Brandes, Ivo Florian; Beissbarth, Tim; Bauer, Martin; Hinz, José
Abstract : Abstract: Hyperglycemia is common during and after Coronary Artery Bypass Graft Surgery (CABGS) and has been shown to be associated with poor clinical outcomes. In this study, we hypothesized that a moderate perioperative mean blood glucose level of <150 mg/dL improves long-term survival in cardiac surgery patients. We conducted a prospective, observational cohort study in the heart center of the University Medical Center of Goettingen, Germany. Patients undergoing on-pump cardiac surgery were enrolled in this investigation. After evaluating perioperative blood glucose levels, patients were classified into 2 groups based on mean glucose levels: Glucose ≥150 mg/dL and Glucose <150 mg/dL. Patients were followed up for 5 years, and mortality within this period was recorded as the primary outcome parameter. Secondary outcome parameters included the length of ICU stay, the use of inotropic agents, the length of hospital stay, and the in-hospital mortality. A total of 455 consecutive patients who underwent cardiac surgery with cardiopulmonary bypass were enrolled in this investigation. A Kaplan–Meier survival analysis of the 5-year mortality risk revealed a higher mortality risk among patients with glucose levels ≥150 mg/dL ( P  = 0.0043, log-rank test). After adjustment for confounders in a multivariate Cox regression model, the association between glucose ≥150 mg/dL and 5-year mortality remained significant (hazard ratio, 2.10; 95% CI, 1.30–3.39; P  = 0.0023). This association was corroborated by propensity score matching, in which Kaplan–Meier survival analysis demonstrated significant improvement in the 5-year survival of patients with glucose levels <150 mg/dL ( P  = 0.0339). Similarly, in-hospital mortality was significantly higher in patients with glucose ≥150 mg/dL compared with patients with glucose <150 mg/dL. Moreover, patients in the Glucose ≥150 mg/dL group required significantly higher doses of the inotropic agent Dobutamine (mg/d) compared with patients in the Glucose <150 mg/dL group (20.6 ± 62.3 and 10.5 ± 40.7, respectively; P  = 0.0104). Moreover, patients in the Glucose ≥150 mg/dL group showed a significantly longer hospital stay compared with patients in the Glucose <150 mg/dL group (28 ± 23 and 24 ± 19, respectively; P  = 0.0297). We conclude that perioperative blood glucose levels <150 mg/dL are associated with improved 5-year survival in patients undergoing cardiac surgery. More studies are warranted to explain this effect.